Localization of eigenvalues for non-self-adjoint Dirac and Klein–Gordon operators. (January 2022) - D'Ancona, P.; Fanelli, L.; Krejčiřík, D.; Schiavone, N.M.
Abstract: This note aims to give prominence to some new results on the absence and localization of eigenvalues for the Dirac and Klein–Gordon operators, starting from known resolvent estimates already established in the literature combined with the renowned Birman–Schwinger principle.